Single transition metal atom stabilized on double metal carbide MXenes for hydrogen evolution reaction: a density functional theory study. (3rd November 2022) - Jin, Di; Hou, Pengfei; Liu, Xiaochun; Tian, Yumiao; Xie, Yu; Du, Fei; Meng, Xing
Abstract: Double metal carbide MXenes have received considerable attention for use in renewable energy storage technologies in recent years. Here, density functional theory calculations were performed to investigate the hydrogen evolution reaction (HER) performances of double metal carbide MXenes (Cr2 TiC2 O2 and the Mo2 TiC2 O2 monolayer (ML) modified by a single transition metal (TM) atom (Co, Ni, Cu, Zn, Rh, Pd, Ag, Cd, Ir, Pt, Au, or Hg)). The thermodynamic stabilities of TM adatoms on pristine Cr2 TiC2 O2 and Mo2 TiC2 O2 MLs and defective Cr2 TiC2 O2 and Mo2 TiC2 O2 MLs with oxygen vacancies (denoted as TM-M′2 TiC2 O2− δ, where M′ = Cr or Mo) were calculated, and the results indicated that the introduction of oxygen vacancies can increase the stabilities of TM adatoms. The TM modification on the MXenes surface tuned the Gibbs free energy of hydrogen adsorption Δ G H, and the Δ G H values of Au-, Co-Cr2 TiC2 O2− δ, and Ni-Mo2 TiC2 O2− δ closed to zero values (0.07, −0.07, and 0.02 eV, respectively). The presence of TM adatoms also changed the reaction mechanism of H2 desorption and reduced the activation barrier for H2 production to improve the catalytic efficiency. Nine TM-M′2 TiC2 O2− δ systems were found to have both HER activity and a lower H2 desorption reaction barrier than the pristine MXenes. Systematic electronic structure analyses showed that charge rearrangement through TM modification could tune the number of electrons gained by the surface O atom and have an impact on the hydrogen adsorption strength. These results indicated that TM surface modification is an effective method for improving the HER catalytic activity of double TM carbides.